Basic interest rate, bank competition and bank spread in personal credit operations in Brazil: A theoretical and empirical analysis - Guilherme Jonas Costa da Silva (EconomiA, 2015)
The debate on the strategy of banking spread reduction in Brazil has been extended for a long time and was fundamentally concentrated in macroeconomics aspects. This paper has the goal of evaluate the new policy of banking spread reduction implemented by the federal government, which has added microeconomic aspects to this tendency. In order to do so, a mathematical model was presented that combines microeconomics aspects, such as was developed by Nakane (2001), with macroeconomics aspects, originally presented by Ho and Saunders (1981). This model was tested for the 25 largest banks in the period of March 2009 to March 2013, using the Panel Data Methodology. The GMM System model was the one that best fitted the data gathered and the results showed that both aspects are relevant in explaining the banking spread in Brazil, and should not be analyzed separately, as is frequently made in the literature, considering the econometric problems related to the omission bias of relevant variables.